The The Development of Training Curriculum to Enhance Competency of Dharma Teaching Based on Active Learning for Monks Teaching Moral in Elementary Schools - Saringkarn, Phrapalad Nontanat; Sithsungnoen, Chanasith (Journal of International Buddhist Studies, 2022)
The objectives of this research were 1) to develop the curriculum 2) to implement the curriculum, and 3) to evaluate the effectiveness of the curriculum. The theoretical and practical sections targeted 15 and 6 monks respectively, through a voluntary selection process. The instruments of the research were 1) knowledge and understanding test 2) evaluation form of designing learning and teaching activities ability 3) evaluation form of teaching ability 4) evaluation form of satisfaction towards the training curriculum. The statistics used to analyze the data were content analysis, percentage, mean, and standard deviation. The research findings were as follows: (1)According to developing the training curriculum, the training curriculum consisted of 7 components; 1) principle 2) objectives 3) content 4) structure 5) learning and teaching activities 6) instruction media, and 7) measurement and evaluation. The training curriculum consisted of 8 units; 1) knowing active learning 2) applying dharma 3) measurement and evaluation 4) media for teaching dharma 5) creative designing 6) teaching for happy learning 7) designing learning and teaching activities, and 8) teaching. The quality of the training curriculum was at the highest level. (2)According to implementing the training curriculum, it was held for 3 days. Pre-test was conducted to evaluate knowledge and understanding before training. After training, evaluating satisfaction towards the training curriculum, doing Post-Test, supervising for 3 times, 5-7 days apart for each time were conducted to collect the data. Teachers were supervisor helpers evaluating teaching of monks teaching moral and evaluating students’ satisfaction. (3)According to the effectiveness of the training curriculum, the results were as follows: 3.1) knowledge and understanding after training was higher than before training 3.2) the progress of designing learning and teaching activities ability was higher in all aspects 3.3) The progress of teaching ability was higher in all aspects 3.4) satisfaction towards the training curriculum was at the highest level.